2020
DOI: 10.20535/2617-9741.2.2020.208054
|View full text |Cite
|
Sign up to set email alerts
|

Surface modification of mixed sorbents with sulfide ions for purification of galvanic wash water of copper plating process

Abstract: Проте, показано, що принцип Гаузе можливо порушити. Наприклад, вирівнювання кількості особи однієї популяції до рівня іншої можливо вже тільки за умови зміни співвідношення факторів народжуваності і смертності. Збалансована конкуренція призводить до поступового вимирання обох популяцій. Отже, якщо цей процес рівномірний, то він буде відбуватися дуже довго, сповільнюючись у часі, допоки ресурсна база не буде відповідати чисельності обох популяцій. Проте, таких сталих умов конкурування у природі не буває і будь-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Regeneration of the spent mixed sorbent (AC+K) after the stage of purification of sugar syrup production of soft drinks was carried out according to the method described in works [6,7]. Methods of purification of water-sugar solutions are described in work [7], sulfide-alkaline solutions -in work [8][9][10][11], washing waters of the electrochemical copper plating process -in work [12]. Regeneration of waste industrial oils was carried out according to the method presented in work [13].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regeneration of the spent mixed sorbent (AC+K) after the stage of purification of sugar syrup production of soft drinks was carried out according to the method described in works [6,7]. Methods of purification of water-sugar solutions are described in work [7], sulfide-alkaline solutions -in work [8][9][10][11], washing waters of the electrochemical copper plating process -in work [12]. Regeneration of waste industrial oils was carried out according to the method presented in work [13].…”
Section: Methodsmentioning
confidence: 99%
“…To increase the sorption capacity, it is popular to modify the sorption matrix using harmless and available reagents. Analysis of recent research and publications [9][10][11][12]13] has shown that the joint processing and disposal of waste from different industries allows you to remove valuable chemical compounds and significantly improve the ecological condition of the environment in their storage. The complex utilization of industrial waste studied today concerns, first of all, reagent extraction of metal cations from sewage of galvanic productions and other chemical wastes by their interaction and formation of waterinsoluble chemical compounds.…”
Section: Introductionmentioning
confidence: 99%